The (Western) South Slavic Language Question Revisited - Peti-Stantić, Anita (Array, 2009)
This paper deals with the revision of the Slavic Language Question. Based on South Slavic data, the author tries to establish new goals of comparative historical standardology, as well as the criteria for a corpus of relevant comparative texts which form the basis of the literary language. Such a corpus follows from established goals and is a consequence of the concrete socio-political and cultural history of certain languages. Special attention is devoted to the essentially different status of Latin in relation to the vernacular languages in the areas under the jurisdiction of the Roman Catholic Church (Slavia romana) and the status of Old Church Slavonic in relation to the vernacular languages in the areas under the jurisdiction of the Serbian Orthodox Church (Slavia orthodoxa). The differences in the status of these two super-ethnic languages determined the differences in the status and corpus of the literary languages that were formed on the basis of the vernaculars in these areas.